Effects of probiotic in drinking water of broiler on growth performance and small intestine villus height - Hanafi, Hanif Hayyi (2017)
The purpose of this study is to provide an alternative additive to substitute the use of antibiotics in broiler diet. This experiment was carried out to evaluate the effects of probiotics on the growth performance and intestinal villus height of the broiler. The experiment used 200 Cobb 500 day old male chicks that were obtained from a local hatchery. It was reared for 42 days at Ladang 2, UPM. The three treatment conducted were control (C, without probiotics), probiotics added on day 18 (T1) and probiotic added on day 21 (T2). Each treatment consisted of six replicates. Probiotic were added in the drinking water of the chicken once they started to drink from the nipple drinker. Laboratory analysis for the villus height and crypt depth were done on three section of the intestine (duodenum, jejunum, and ileum) after the broilers were slaughtered on day 42. Based on the results obtained, there were no significant difference (P > 0.05) on the growth performance across all treatment. However, there were significant difference (P > 0.05) in the small intestine villus height and crypt depth at the jejunum region. T1 was significantly higher for both villus height and crypt depth at the jejunum region. At the ileum region only the crypt depth were significant between the treatments. The duodenum region showed no significant difference. T1 reflect a better result when compared to T2 and control in terms of villus height and crypt depth. This study showed that probiotic helped to induce a better gut morphology in terms of villus height and crypt depth although there was not much influence of the probiotics on the growth performance. Birds that are exposed to the probiotic at earlier stage showed better result.